Disponibilidade de minerais, germinação e vigor de sementes de milho - Magalhães, Stefânia Caixeta [UNESP] (2009)
Most of the traditional methods used for seed vigor evaluation are qualitative and, as such, prone to errors and results misinterpretation. Quantitative methods may constitute more reliable alternatives. The aim of this work was to verify if the concentrations of some minerals stored in the seeds and made available during the initial stages of the germination process constitute sensitive and reliable indicators of the level of corn seed vigor. Twenty seed lots were evaluated by means of the germination, electrical conductivity, cold and seedling field emergence tests. Additionally, the concentrations of inorganic phosphorus, phosporus, calcium, potassium and magnesium at 12 h, 24 h, 36 h and 48 h after the initiation of the germination process were also evaluated by means of the injection analysis in flow (FIA) and the spectrometry of optic emission coupled to plasma of induced argon (ICP-OES) techniques. For these analyses grinded seed samples were extracted with water at 95ºC, agitated for 30 minutes and centrifuged . It was concluded that the concentrations of Pi, P, Ca, Mg and K, extracted by the warm water method, in hybrid corn seeds after certain stages of the germination process, allowed the rating the of seed lots in a way similar to that obtained with the results of several other seed vigor tests. Specifically, this was achieved by evaluating the concentratrions of Pi after 12 h and 48 h, of P after 12 h, 36 h and 48 h, of Ca after 24 h, 36 h and 48 h, of Mg after 36 h and 48 h and of K after 36 h and 48 h after the beginning of the germination process.